Digitally fabricated ribbed concrete floor slabs: a sustainable solution for construction - Mata-Falcón, Jaime; Bischof, Patrick; Huber, Tobias; Anton, Ana; Burger, Joris; Ranaudo, Francesco; Jipa, Andrei; Gebhard, Lukas; Reiter, Lex; Lloret-Fritschi, Ena; Van Mele, Tom; Block, Philippe; et al. (RILEM Technical Letters, 2022)
The concrete used in floor slabs accounts for large greenhouse gas emissions in building construction. Solid slabs, often used today, consume much more concrete than ribbed slabs built by pioneer structural engineers like Hennebique, Arcangeli and Nervi. The first part of this paper analyses the evolution of slab systems over the last century and their carbon footprint, highlighting that ribbed slabs have been abandoned mainly for the sake of construction time and cost efficiency. However, highly material-efficient two-way ribbed slabs are essential to reduce the environmental impact of construction. Hence, the second part of this paper discusses how digital fabrication can help to tackle this challenge and presents four concrete floor systems built with digitally fabricated formwork. The digital fabrication technologies employed to produce these slab systems are digital cutting, binder-jetting, polymer extrusion and 3D concrete printing. The presented applications showcase a reduction in concrete use of approximately 50% compared to solid slabs. However, the digitally fabricated complex formworks produced were wasteful and/or labour-intensive. Further developments are required to make the digital processes sustainable and competitive by streamlining the production, using low carbon concrete mixes as well as reusing and recycling the formwork or structurally activating stay-in-place formwork.